Peningkatan pembelajaran dasar long serve menggunakan metode inquiry dalam permainan bulutangkis - Alimuddin Alimuddin; Nurhidayah Hasyim; Liza Liza; Yahya Eko Nopiyanto (Universitas Riau, 2022)
The efficiency of providing long serve learning materials is still very lacking in students of Padang City Junior High School. With the lack of efficiency resulted in the learning of the main sport of badminton is still less accurate. The main purpose of the research conducted is to find out the improvement of Basic Long Serve learning using inquiry methods in Badminton Games. The type of research that is done is class action research. The sample in this study was as many as 30 students of Padang City Junior High School. The research instrument used is a test instrument for the learning ability of long serve badminton games. The data analysis technique used is comparative descriptive analysis. Based on the results of research that has been carried out from cycle I obtained as many as 11 students (36.7%) completed and 19 students (63.3%) incomplete. While in cycle II showed an increase of 25 students (83.3%) completed and 5 students incomplete (16.7%). Based on the average results that have been obtained, it can be said that there is an increase from cycle I to cycle II. Sothe conclusion that can be obtained from this study is the basic learning of long serve in badminton games through inquiry methods in padang city junior high school studentsCopyright © The Author (s) 2022Journal of Sport Education (JOPE) is licensed under a Creative Commons Attribution-ShareAlike 4.0 International License.